Association of inflammatory markers and endothelial dysfunction with depression in patients with ischemic cerebrovascular disease - Julcileia Imara D De Carvalho Muenho; Marisol Peña Sanchez; Alina González-Quevedo Monteagudo; Danay Martínez Puentes; Sergio González García; Marianela Arteche Prior; Asdrubal Arias Morales (Medisur)
Foundation: depression in ischemic cerebrovascular disease is one of the most frequent non-neurological complications. Objective: to determine the association of inflammatory markers and endothelial dysfunction with depression in patients with ischemic cerebrovascular disease. Methods: an analytical, prospective, cross-sectional study was carried out in patients with acute (N=22) and non-acute (N=37) ischemic cerebrovascular disease; treated at the Institute of Neurology and Neurosurgery; and the Manuel Fajardo Hospital, in Havana, Cuba. Demographic variables, risk factors, etiology and location of the infarction, neurological deficiency, disability for activities of daily living (Barthel index), neuropsychological (depression by Beck inventory and Hamilton test) were collected. C-reactive protein, alpha-1-antitrypsin, C3 and C4 complements, and microalbuminuria were determined. Results: the scores of the neuropsychological tests did not have significant differences between the acute and non-acute phase, but there was a statistical increase in the frequency of patients without depression and with slight depression in the non-acute phase. In the acute phase, C4, and in the non-acute phase, C3, C-reactive protein and alpha-1-antitrypsin were directly correlated with the Beck inventory score. C-reactive protein and C3 were statistically correlated with the Hamilton test score. In the multivariate analysis, C-reactive protein showed an independent association with the degree of depression by the Hamilton test. Conclusions: C-reactive protein could be related to the severity of depression, perhaps by association with the disability for activities of daily living.